(untitled) (Bodhi Path, 2020)
Everybody wants to be happy but happiness cannot be achieved in isolation since everybody depends upon others. This is because that life is interdependent on one another.In order to be happy that one have to depend upon the cultivation of wholesome attitude towards all in the society and also ultimately all other sentient beings. The best way of cultivating wholesomeness for sentient beings is meditation as preached by The Enlightened Buddha. The cultivation of sublime attitudes of mind towards all is single out as loving-kindness unconditionally, compassion, sympathetic joy and equanimity as taught by the Enlightened Buddha to the extent of limitlessness and removes all ill will, cruelty, jealousy, hatred, craving and desire which are caused due to self grasping ignorance. Ignorance is the root cause of all miseries. The Buddha, the enlightened and awakened one preached his first ever teachings to the group of Bhikkhus-the pañcavaggiye Bhikkhu namely Kondañña, Mahanāma, Bhadai, Vappi and Asjit.They all are old colleagues of Siddhartha who later on be known as The Enlightened Buddha during the period of meditation when he wandering in search of the path to rid of the sufferings of the human beings. The Enlightened Buddha preached all of them the sublime virtue, cause and effect (Paṭiccasamuppāda), impermanence (aññatta) and egolessness (anātāman) and never-ending or illimitable (appamaññā), at Isipattaṃ Migdaya, the arranyā (grave) situated in Sarnath near Varanasi after achieving perfect Enlightenment under the Bodhi Tree sitting on the vajrāsana, the diamond throne with strong determination on the bank of river Niranjanā also known as Phāggu in Bodh Gayā. All monks achieved Nibbāna and they all are free from all kinds of worldly elusion and delusion and ultimately from all sufferings, after having benefitted by the teachings of the Enlightened Buddha and they all transmigrated in Arahathood. They were abode in sublime state after achieving Nibbāna. This is the extreme state of equanimity and the crown of the best state of the four sublime abodes and these are also known as Four Immeasurables. In Buddhism, all these states are treated as cardinal virtues. The message of the Enlightened Buddha is that of loving kindness unconditionally and compassion. All human beings must be loved unconditionally just like a mother loves her new born son to the depth of her heart. She saves her son from all kind of disparities. The great loving kindness and compassion is the spirit to save all human beings from all kind of harms by any and all means. No one harm any human beings at any cost. The unconditional love and compassion is the courage that prompts good will among the people those suffer with their sufferings. Such as the Enlightened Buddha preached dacoit Aṅgulimāla and trained him for sublime abodes and also transmigrated him into a noble monk, Arahat. Aṅgulimāla was given up all his cruelty that he vowed to kill one thousand men as he has to fulfil his Gurūdakshanā, the parting- gift to his teacher against the people of Sāvatthī. (Aṅgulimāla Sutta in the Majjhima Niakaya). He also preached Devadutta with love and compassion all the time even though Devadutta intending always to kill him by one tactics or the other. He unleashed intoxicated Nālāgiri elephant intending to kill the Enlightened Buddha but He was not afraid at all but subdued the intoxicated elephant with love, kindness and compassion. The intoxicated Nālāgiri elephant fell on the foot of the Enlightened Buddha and calm down and respectfully bow his head in the honour of Buddha. The Blaze of Non-Dual Bodhicitta-H.H.The Dalai Lama, Tibet House, New Delhi